Employee Wellbeing: Evaluating a Wellbeing Intervention in Two Settings - Keeman, Alexis; Näswall, Katharina; Malinen, Sanna; Kuntz, Joana (Frontiers in Psychology, 2017)
This research presents two studies conducted to evaluate the Wellbeing Game in two different contexts: in a student sample and in an organizational setting. Study 1 investigated the efficacy of the Wellbeing Game, in terms of its effect of wellbeing, stress and an image valence test, among 60 university students. The results showed that after playing the Wellbeing Game, students reported a significant positive change in wellbeing compared to those who did not play the Wellbeing Game, but there was no decrease in stress or any change in classification of image valence. Study 2 evaluated the Wellbeing Game in an organizational context. Employees (n=52) in a financial organization played the Wellbeing Game for four weeks and answered survey questions about wellbeing and stress at the beginning and end of this period. The results showed that after playing the Wellbeing Game, employees reported lower stress levels, and higher wellbeing levels for those who felt that it had helped them connect more with colleagues. The results from the two studies provide preliminary support that the Wellbeing Game may be an effective wellbeing intervention tool in both an organization and a non-organizational context.